Peningkatan pemahaman konsep kegiatan ekonomi dan jenis-jenis usaha melalui model pembelajaran kooperatif tipe example non example pada peserta didik kelas V sekolah dasar - Oktaviana Anisha; Hadi Mulyono; Hadiyah Hadiyah (Didaktika Dwija Indria, 2020)
The direction of this research is to improve concept understanding of economy activity and types of bussines through the implementation of cooperative learning model type example non example in grade 5 of primary education. This research is a classroom action research consist of two cycle. The subject of this research is grade  students of SD Negeri 2 Manggis that totaling 33 students. The techniques of accumulation data in this research were observation, interviw, tests and documentation, with data analysis using content validity testing and triangulation technique. The cycle 1 in this research resulted a classical completeness of 54,55%, continuing in classical completeness in cycle 2 which increased to 81,82%. Based on the output, can be summarize that the use of cooperative learning model type example non example can improve the concept understanding of economy activity and types of business in grade 5 of SD Negeri 2 Manggis 2019/2020 academic year.Keywords: concept understanding, economy activity and types of business, example non example, primary education